Financial Behavior as Key Factors Affecting Indonesian Gen-Z Entrepreneurial Intention - Candy, Candy; Vira, Vira (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
This research intends to investigate the effects of financial knowledge, self-control, parental socialization, and peer influence on the entrepreneurial intention of Generation Z (Gen-Z) through saving behavior as the mediating variable. A sample size of 396 Indonesian Gen-Z were used, and SmartPLS 3.0 program was adopted to evaluate the collected information. Meanwhile, structural equation model was implemented based on the partial least square method. The results reveal that financial literacy, self-control, and parental socialization positively affect saving behavior and successfully intervene entrepreneurial intention. However, peer influence has no significant connection to saving behavior and entrepreneurial intention. A novel framework is offered to policymakers to identify the driving forces of Gen-Z propensity to save and pursue entrepreneurial opportunities.